2017
DOI: 10.1111/aeq.12190
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Cultural Diversity and Special Education in Catalonia: The Subtle Production of Exclusion through Classroom Routines

Abstract: Drawing on ethnographic data collected in two primary schools, this paper examines the nature of the exclusion experienced by three children of linguistically, culturally, and socioeconomically diverse families labeled as having special education needs. Ambiguities and dilemmas surrounding the intersection of cultural diversity and special education are described, and ways in which the routines performed in mainstream classrooms produce a seemingly harmless, but pervasive, form of exclusion are discussed. [spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…They also emphasised that there were differences between districts, where migrant populations had had a longer presence and that younger generations of teachers seemed to have a more open mind about cultural diversity and integration in schools. Similarly, Migliarini (2018) and Paniagua (2017) noted the increasingly diverse intake of schools in Italy and Spain, and showed how the perceptions of teachers may affect migrant children in terms of assessment and SEN provision. Migliarini (2018) describes what she calls the 'SENitization' of migrant children -a process whereby the children's illiteracy and disrupted schooling is defined as a disability.…”
Section: Multi-cultural Understanding and Readinessmentioning
confidence: 95%
See 1 more Smart Citation
“…They also emphasised that there were differences between districts, where migrant populations had had a longer presence and that younger generations of teachers seemed to have a more open mind about cultural diversity and integration in schools. Similarly, Migliarini (2018) and Paniagua (2017) noted the increasingly diverse intake of schools in Italy and Spain, and showed how the perceptions of teachers may affect migrant children in terms of assessment and SEN provision. Migliarini (2018) describes what she calls the 'SENitization' of migrant children -a process whereby the children's illiteracy and disrupted schooling is defined as a disability.…”
Section: Multi-cultural Understanding and Readinessmentioning
confidence: 95%
“…However, the teachers in Paniagua's (2015) study from Spain also found the curriculum too rigid and the time too limited to coordinate and look for alternative practices. Paniagua (2017) furthermore describes the difficulties experienced by children with SEN in relation to time-measured task and correction of homework, both tasks derived from curricular constraints and the need to save time.…”
Section: The School Systemmentioning
confidence: 99%
“…The intersectionality of identity means that ways of enacting one aspect of a social identity may conflict or intersect with another aspect, especially as connected to awareness of membership in a group, the value placed on that membership, and emotional investment in that membership (Ashcraft et al ; Han ; Paniagua ; Tajfel ). For example, individuals who face discrimination because of their minority background may choose not to speak their home language if it signals their minority group membership to others (Shin ).…”
Section: Constructing Inclusive Identities Through Educationmentioning
confidence: 99%
“…OECD's landmark study Teachers Matter (OECD, 2005 [1]) described the main concerns that were common in OECD countries regarding teacher policies, and advanced a number of key areas for action. Regarding early career teachers, the report highlighted the need to better support new teachers, to align initial teacher education, induction programmes, and continuous professional development, and to address the significant research gaps concerning the context of teachers in different countries.…”
Section: Early Career Teachers As De Facto Teacher Residency: Concludmentioning
confidence: 99%
“…It is common that teachers will spend their early years of teaching in a series of temporary positions, in a variety of schools -which are likely to be the most challenging -and therefore they do not have the possibility to know the particular school culture or to establish supportive professional relationships. Improvement measures to stabilise early career teachers -as it is the case of teacher replacement pools where substitute teachers are assigned permanently to schools while they don't work as substitutes (OECD, 2005 [1]) -would potentially ease the transition from initial teacher education to schools.…”
Section: In-service Teachersmentioning
confidence: 99%